Bài toán NP-đầy đủ đối với lưới Petri – suy rộng dưới dạng SM (self-modifying –net) thuộc lớp PSMonce - Chau, Tran Tho (Journal of Computer Science and Cybernetics, 2018)
In this paper we show that the k-bounded problem for self-modifying-nets in PSMonce is NP –complete.